Розкопки ґрунтового могильника доби бронзи та давньоруського часу в с. Лючин на Рівненщині - Самолюк, В.О. (Археологічні дослідження в Україні, 2009)
In 2008, the research of burial ground with graves of the Bronze Age and Ancient Rus period accidentally discovered in Lyuchyn village of Ostrih Region in Rivne Oblast was ongoing. 10 graves were revealed, five of which were referred to the epi-Corded Ware culture period and five to the Ancient Rus time. Three copper adornments in the form of willow leaves are of a special attention, two of which has the form not known before.